AN ANALYSIS OF DEFINITION AND DESCRIPTION CONCEPT IN SCIENTIFIC ARTICLE - RAMADHANI, GITA; SYAHREZA, HADIAN FIRMAN; PANGARIBUAN, WANAPRI; MUDJISUSATYO, YUNIARTO (Universitas Negeri Medan, 2024)
The concept of definition is a basic discussion in a study. The objectives of this study is to analyse the definition and description concept contained in scientific article. The definition and description is considered as an important thing to comprehend the concept of discussion. The analyzed article is entitled œEffects of Educational Management on Quality Education in Rural and Urban Primary Schools in Ghana Heliyon Journal published by Elsevier Ltd. This research uses a qualitative descriptive method and a theory from Miles and Huberman as a technique of data analysis. There are five data found in article classified as a definition and description. The result shows that all the data categorized as a real definition and there is no nominal definition in the article.